2019
DOI: 10.5530/pj.2019.11.157
|View full text |Cite
|
Sign up to set email alerts
|

Some Pharmacognostic Studies of the Bird Cherry (Padus avium Mill.) and Mountain Ash (Sorbus aucuparia L.) Fruits Collected from Moscow (Russia)

Abstract: Background: Light microscopic analysis is appropriate pharmacopoeial method for quality control of fresh and fast-frozen Rosaceae family plants fruits. It is widely used for crude herbal drugs analysis and helps to identify significant anatomical and diagnostic signs. The aim of the research was to establish the identity characteristics of the dried and frozen fruits of mountain ash and bird cherry and to perform phytochemical analysis of studied objects harvested in Moscow. Materials and methods: Light micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Sergunova and Bocov [14] reported that the profile of organic acids in rowan fruits consists of the following acids: malic, citric, oxalic, succinic, tartaric, ascorbic, fumaric, quinic, and sorbic. Other authors have also shown that malic and citric acids reach significant amounts in the fruits of this species-2854.4 mg/kg and 1089.7 mg/kg respectively [15].…”
Section: Polyphenol and Carotenoid Composition Antioxidant Activity And Carotenoid Bioaccessibility In Rowan Extractsmentioning
confidence: 99%
“…Sergunova and Bocov [14] reported that the profile of organic acids in rowan fruits consists of the following acids: malic, citric, oxalic, succinic, tartaric, ascorbic, fumaric, quinic, and sorbic. Other authors have also shown that malic and citric acids reach significant amounts in the fruits of this species-2854.4 mg/kg and 1089.7 mg/kg respectively [15].…”
Section: Polyphenol and Carotenoid Composition Antioxidant Activity And Carotenoid Bioaccessibility In Rowan Extractsmentioning
confidence: 99%
“…Interestingly, our results for glucose and fructose, as well as for total sugar content (6.36 g/100 g fw), were comparable to those in other studies on forest fruits, such as bird cherry (Padus avium Mill. ), mountain-ash (Sorbus aucuparia L.) (Sergunova and Bokov, 2019), blackthorn (Prunus spinosa L.) (Sikora et al, 2013), some Sorbus cultivar (Zymone et al, 2018), blueberry (Akšić et al, 2019), blackberry, strawberry, wild-grown elderberry and goji berry (Mikulic-Petkovsek et al, 2012). Sweetness Index -SI was 11.08, while TSI was 7.52 (Table 1).…”
Section: Nutritional Characteristics Of Common Whitebeam (Sorbus Aria) Fruitmentioning
confidence: 99%